Povezanost 24-urnega krvnega tlaka z razvojem športnega srca pri ženskah in moških - Rogel, Polona (Medicinski razgledi, 2003)
Long term athletic training is associated with an increase in left ventriculardiastolic cavity dimensions, wall thickness, and mass. These changes are described as the "athlete's heart". In men, athlete's heart is more frequently present than in women. We decided to test the following hypotheses: 1. Increased left ventricular mass in male athletes is related to higher blood pressure. 2. Increased left ventricular mass in male athletes is not related to intensity of training. 15 pairs of national sport dancing team and 30 control subjects (15 males, 15 females), were studied. In all subjects casual and 24-h ambulatory blood pressures, echocardiography and maximal stress testing were performed. Female in comparison to male dancers had significantly lower M-mode (p < 0.004) and 2D left ventricular mass index (p <0.001), 24-h systolic blood pressure (p < 0.001), day (p < 0.001) and night systolic blood pressure (p < 0.001), and casual systolic blood pressure (p < 0.000) and achieved significantly lower systolic blood pressure at maximal level of stress testing (p < 0.004). Multiple stepwise regression analysis showed that the best predictors of 2D left ventricular mass index are maximal work load and peak exercise systolic blood pressure, 24-h systolic blood pressure, day and casual systolic blood pressure. Lower left ventricular mass index in female dancers can be partly explained by lower systolic blood pressures during 24-h and at exercise. Gender difference in left ventricular mass index is not related to the intensity of training, which is in sport dancing the same in both members of the pair.
Keywords: Hipertrofija levega prekata; Sports; Hypertrophy, Left Ventricular; Krvni pritisk, merilniki; Krvni pritisk, merjenje; Dancing; Blood Pressure Determination; Ples; Blood Pressure Monitors; Športi; Exercise Test; Multivariatna analiza; Obremenitveni test; Sex Factors; Odrasli; Adult; Heart Rate; Spolni faktorji; Multivariate Analysis; Srčna frekvenca; krvni tlak; heart; srce; športniki